MARKETING EFFECTIVENESS USING SOCIAL MEDIA IN MOIKAFOOD CIMAHI - Dhe Lelly Prayadi Putri; Budi Prasetiyo (Media Inovasi Pendidikan dan Publikasi, 2023)
This study aims to examine the effectiveness of marketing through social media at UMKM Moikafood Cimahi with a qualitative research approach. MSMEs (Micro, Small and Medium Enterprises) have played an important role in local economic growth, and the utilization of social media as a marketing tool has become an increasingly popular strategy for MSMEs to reach potential customers. This study was conducted using a qualitative research method involving in-depth interviews with Moikafood MSME owners and several members of the marketing team who are responsible for social media utilization. In addition, participatory observations were also made to understand marketing practices carried out through social media platforms.